(untitled) (Journal of Shaheed Suhrawardy Medical College, 2013)
Lymphangitic carcinomatosis is an uncommon manifestation of metastasis to lung. Its presentation can mimic several disorders of the lungs. A case is presented here where patient presented with progressive dyspnoea, dry cough, weight loss and fever. The patient was amenorrheic for the last 2 years. Her physical findings were unremarkable initially other than the weight loss and evidence of pulmonary hypertension. Subsequently her dyspnoea rapidly worsened and the patient became bed bound. Investigations revealed neutrophilic leucocytosis, normal Hb with high ESR. ANA, anti Cetromere and anti Scl 70 was negative. Serum calcium was normal. Liver function test was normal other than raised alkaline phosphatase. Tuberculin test was negative. Chest X-ray revealed increased bilateral symmetrical streaks and reticulation with peripheral and lower distribution which is consistent with pulmonary lymphangitic carcinomatosis. HRCT of Lungs has shown diffuse infiltrations, reticulo-nodular and ground glass opacities, centrilobular emphysema with accentuation of broncho-vascular densities in both lung fields. There were enlarged mediastinal lymph nodes, bilateral pleural effusion. Doppler Echo revealed mild pulmonary hypertension with fair EF. Tumor markers were done. CA125, CA 19.9 and AFP were ten times higher than normal. Fibreoptic nasopharyngoesophagoscopy was normal. Diagnosis of PLC was made on clinical feature, radiological finding and elevated tumor markers. Symptomatic treatment was given during the period of evaluation. Ultimately the patient succumbed to death. DOI: http://dx.doi.org/10.3329/jssmc.v5i2.20769 J Shaheed Suhrawardy Med Coll, 2013;5(2):114-116